PENGARUH QUALITY WORK OF LIFE DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMENEP - Kurniawati, Dina; Abrar, Unsul (Economos : Jurnal Ekonomi dan Bisnis, 2020)
The aspect of human resources is an important aspect in an organization and bureaucracy at this time, thus it is expected that the quality work of life with work discipline is able to provide encouragement and positive effect for the development of performance in several related agencies. The office which is engaged in public services that focuses on services to the general public requires an adequate quality work of life (QWL) for its employees. So that, assurance of the quality of work life of employees will have a good impact on employee performance. The quality of work that needs to be considered includes participation in decision making, opportunities for self-development, adequate income, and last education level. And it will be achieved if the relationship between leaders and subordinates is very good. The purpose of this study is to find out whether there is an effect of quality work of life and work discipline on employee performance, and whether there is an effect of quality work of life on work discipline. The data analysis technique in this study used Partial Least Square (PLS) with the help of Smart PLS 2.0 M3 software. PLS as a general method to estimate paths model using latent variables with multiple indicators.